Exploring EFL Teacher Trainers’ Perceptions on the Practicum: Realities and Future Directions - ZEGHMAR, Racha; DJOUIMA, Leila (Journal of Human Sciences, 2025)
Practicums are considered to be essential in English as a Foreign Language (EFL) pre-service teacher training programs, allowing emerging teachers to use and practice their newly gained pedagogical knowledge. This study investigates the perceptions of EFL teachers at Ecole Normale Superieure de Constantine (ENSC) and Ecole Normale Superieure de Bouzareah (ENSB) on their trainees’ practicum experience as well as the current state of the pre-service teacher training practicum in EFL education. Furthermore, it examines how these teachers perceive the practicum’s role in enhancing their trainees’ pedagogical knowledge and teaching abilities and seeks to identify the challenges trainees encounter throughout their practicum experience. Further, it collects recommendations from these teachers on potential improvements to optimize the training program for future cohorts. To achieve the aforementioned objectives, an online survey was conducted with a purposive sample of eight ENSC and five ENSB teachers, uncovering a range of insights regarding the practicum. While some educators embrace the current practicum, others report some limitations that need to be taken into account. Their valuable insights underscore the potential impact that a wider contribution from the teaching community could have. Given all that, the findings reveal that while the practicum is valuable for trainees, there are several areas for potential improvement. This highlights the necessity for Algerian practicums to be revised and updated, so as to bridge the gap between theory and practice and reassure a successful teaching experience that meets learners’ needs.